Lesões hepáticas na leishmaniose visceral canina: aspectos histopatológicos e bioquímicos - Castro, Igor Paula de (2012)
The present study describes the histopathological changes in liver of dogs with leishmaniasis, assessing the predominant inflammatory infiltrate, parasite load and the degenerative changes and correlate them with clinical symptoms and serum biochemical changes. A total of 50 dogs, 17 negative (control group) and 33 seropositive for leishmaniasis, classified as asymptomatic, oligosymptomatic or symptomatic. From the collection of 10 mL of blood in tubes without anticoagulant and the serum extracted, were determined the concentrations of total protein, albumin, ALT, alkaline phosphatase and GGT. Later the animals were euthanized and liver fragments were collected for histopathologic analysis. From the histopathological evaluation of liver tissue, it was found that the major degenerative changes were observed fatty degeneration and cellular edema, with no difference between groups of animals symptomatic, asymptomatic and oligosymptomatic (p ≤ 0.05). There was no difference in incidence of inflammatory infiltrate between the three groups, nor in relation to the number of infected cells. Regarding the assessment of serum biochemical changes, all three groups showed increased values of GGT, total protein and globulin and decreased albumin. Animals naturally infected by Leishmania may have inflammatory and degenerative changes in the liver, but without presenting clinical symptoms. Hypoproteinemia associated with hyperglobulinemia, and increased levels of GGT in animals occur both symptomatic and asymptomatic and oligosymptomatic.